ANALISIS IDENTITAS MEREK, LOYALITAS MEREK, CITRA MEREK, DAN KEPERCAYAAN MEREK TOYOTA - Ade Jermawinsyah Zebuah (Institute of Research and Community Outreach - Petra Christian University, 2018)
Consumer needs in vehicles is increasing, it triggers any car companies to create great brand identity in order to gain brand trust from consumen. Perception of brand from consumen is affect to gain brand trust which is have great deal to brand loyalty. This research is aiming to analyze the influence of brand identity on brand loyalty with brand image and brand trust as an intervening variable. This research will be done by distributing 100 questionnairs to the respondents who have buy or used Toyota. Analysis techniques that will be used is quantitative analysis with Smart-PLS method. Research shows that brand identity influences brand image, but has no influences to brand trust, brand image influences brand trust. Also brand image and brand trust influences loyalty of Toyota’s brand.